The contribution of private land conservation to 30x30 in Germany - Kopsieker, Lisa; Disselhoff, Tilmann (Frontiers in Conservation Science, 2024)
In line with Target 3 of the Kunming-Montreal Global Biodiversity Framework, the European Union (EU) aims to protect 30% of its land and sea by 2030 (known as 30x30). Germany has been a vocal supporter of this goal in the international arena but has yet to achieve sufficient protected area coverage domestically. We estimate that Germany needs to report an additional 4.65 million hectares of protected land to achieve 30x30. This article examines the potential of privately protected areas (PPAs) and other effective area-based conservation measures (OECMs) to contribute to this goal. We explore the German Federal Nature Conservation Act and identify the legal hurdles for the designation and recognition of PPAs. Furthermore, we argue that OECMs have the potential to contribute significantly to 30x30 in Germany. We estimate that close to one million hectares of land could be classified as OECMs and outline potentially qualifying sites. In conclusion, we discuss the prerequisites for upscaling private land conservation in Germany, focusing on required conditions for establishing OECMs and incentivising conservation easements and long-term conservation leases through national funding programmes.